The Relation of Discourse Analysis about Rohingya News - Mandarani, Vidya; Nuroh, Ermawati Z.; Alfarisi, Irham Salsabila; Khumairoh, Tahnian Eka; Alfarisy, Istia Hajar (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Language plays an important role in human life in shaping discourse. Media forms the discourse to the community. Language elements that form the discourse of news according to Van Dijk include macro, superstructure and micro analysis. One of the news that concerns the public is the news about Rohingya. Discourse analysis of the news about Rohingya is very important to do because Rohingya news contains political discourse, religion and ethnic conflicts that shape public opinion after reading, seeing or hearing news about Rohingya case. This research was conducted to be able to know in depth the discourse of Rohingya news from three different media namely VOA, Jakarta Post E-paper version and CNN. The purpose of the selection of these three media is the discourse of Rohingya news can be analyzed from different types of news, from the print version, online version and news version on television. This research uses qualitative descriptive method because the researcher will directly find how is the discourse in 3 types of media that is print, online and television. The results of this study, from the textual analysis can be seen that every news program has a different theme in shaping the discourse in this case the news about Rohingya. The news of The Jakarta Post E-paper, VOA News and CNN News have the same discussion about Rohingya cases. The result of the analysis of macrostructure, superstructure and microstructure showed that there is different way to present the news but the theme is conical on the same discussion that is the religion problem in Rohingya and the victims of the conflict in struggling for the human right.